2016
DOI: 10.21037/jtd.2016.12.20
|View full text |Cite
|
Sign up to set email alerts
|

Segmental bronchi collapsibility: computed tomography-based quantification in patients with chronic obstructive pulmonary disease and correlation with emphysema phenotype, corresponding lung volume changes and clinical parameters

Abstract: Background: Global pulmonary function tests lack region specific differentiation that might influence therapy in severe chronic obstructive pulmonary disease (COPD) patients. Therefore, the aim of this work was to assess the degree of expiratory 3 rd generation bronchial lumen collapsibility in patients with severe COPD using chest-computed tomography (CT), to evaluate emphysema-phenotype, lobar volumes and correlate results with pulmonary function tests.Methods: Thin-slice chest-CTs acquired at end-inspiratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…McDonough et al [44] found that small conducting airways (<2.0 mm) in COPD become narrow and disappear before the onset of emphysema. Previous reports have asserted that these abnormalities in small airways will be reflected in large-and intermediate-sized airways [45]- [47]. A reduced tracheal section, total airway count on CT and airway branch variation have been proposed as the independent and innate risk factor of COPD [17], [19], [20], [43].…”
Section: A Pathophysiological Rationale Of Airway Abnormalities In Copdmentioning
confidence: 99%
“…McDonough et al [44] found that small conducting airways (<2.0 mm) in COPD become narrow and disappear before the onset of emphysema. Previous reports have asserted that these abnormalities in small airways will be reflected in large-and intermediate-sized airways [45]- [47]. A reduced tracheal section, total airway count on CT and airway branch variation have been proposed as the independent and innate risk factor of COPD [17], [19], [20], [43].…”
Section: A Pathophysiological Rationale Of Airway Abnormalities In Copdmentioning
confidence: 99%
“…The treatment with GLP-1R agonists was also effective on secondary outcomes, as it significantly improved FVC, MEF 75 and MEF 50 , but not MEF 25 . The lack of effectiveness on MEF 25 , a variable that measures the flow rates at low lung volume providing the physiological assessment of small airways function [31,32], can be explained by considering that in humans the GLP-1R is expressed on the ASM of medium airways (segmental bronchi) but not in small airways (bronchioles) [30]. Interestingly, in the control cohort, the treatment with metformin alone not only elicited a numerical improvement of FEV 1 , but also significantly improved FVC.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, different morphologic and functional methods have been proposed, which are mostly based on the differentiation of homogeneous and heterogeneous emphysema phenotypes (16,18,19). While this differentiation can be performed visually on high-resolution CT images of the chest, quantification of lung parenchymal density may be more accurate, and calculation of the distribution of emphysema equivalent areas has become practicable based on the so-called "cluster analysis" (20). In order to understand which impact the interplay of different lobar phenotypes could potentially have in a patient, we performed lobar-based phenotype analysis of the targeted lobe, and also of the nontargeted ipsilateral and contralateral lung lobes.…”
Section: Discussionmentioning
confidence: 99%